Microbiological Profile and Antimicrobial Susceptibility Patterns in Patients with Tinea Pedis at Diabetic Center In EL-Beyda City - Souad ALtabouli,; Salema Qowaider,; Manal Hamad,; Marfoua Ali, (AlQalam Journal of Medical and Applied Sciences, 2024)
The purpose of this study was to determine the microbiological profile and antimicrobial susceptibility patterns in patients with Tinea Pedis at the Diabetic Center in EL-Beyda City (Libya). Samples were collected from the diabetic patients with intertrigo of foot attending the out-patients’ department in the Diabetic Center from December 2020 to February 2021 by using sterile swabs. Samples were inoculated into blood and MacConkey agars for bacterial isolation. The microbiologic isolation and antimicrobial susceptibility tests were performed according to standard microbiological methods. Antibiotic susceptibility patterns of all the isolates to different antibiotics was determined by antimicrobial susceptibility testing. Overall, 50 patients (50% male and 50% female) had a mean age of 58.4 ± 9.4 years and a mean duration of diabetes of 14.6 ± 6.6 years. Most isolates (76.8 %) were Gram-negative bacilli (Escherichia coli, Pseudomonas aeruginosa, Klebsiella Spp and Proteus Spp), followed by Gram-positive cocci (23.2%) (Streptococci Spp and Staphylococcus aureus). Most bacteria were sensitive to Ciprofloxacin (84.0%) and resistant to Erythromycin (42.0%). The majority of isolated bacteria from patients were found to be multi-drug resistant. The results demonstrate the importance of time in the identification of the intertrigo sample collection for the identification of the pathogens and their antibiotic susceptibility pattern before initiating antimicrobial treatment. الغرض من هذه الدراسة هو تحديد المظهر الميكروبيولوجي وأنماط الحساسية المضادة للميكروبات لدى المرضى الذين يعانون من سعفة القدم في مركز مرض السكري في مدينة البيضاء (ليبيا). تم جمع العينات من مرضى السكري الذين يعانون من ثنية القدم المترددين على قسم العيادات الخارجية بمركز السكري في الفترة من ديسمبر 2020 إلى فبراير 2021 باستخدام مسحات معقمة. تم تنمية العينات في الاوساط الغذائية التالية الدم وأجار ماكونكي لعزل البكتيريا. تم إجراء اختبارات العزلة الميكروبيولوجية واختبارات الحساسية المضادة للميكروبات وفقا للطرق الميكروبيولوجية القياسية. تم تحديد أنماط الحساسية للمضادات الحيوية لجميع العزلات للمضادات الحيوية المختلفة عن طريق اختبار الحساسية للمضادات الحيوية. بشكل عام، كان متوسط عمر 50 مريضًا (50% ذكور و50% إناث) 58.4 ± 9.4 سنة ومتوسط مدة الإصابة بالسكري 14.6 ± 6.6 سنة. معظم العزلات (76.8%) كانت عصيات سلبية الجرام (Escherichia coli, Pseudomonas aeruginosa, Klebsiella Spp and Proteus Spp) تليها المكورات موجبة الجرام بنسبة (23.2 %) (Streptococci Spp and Staphylococcus aureus) كانت معظم البكتيريا حساسة للسيبروفلوكساسين بنسبة (84.0%) ومقاومة للإريثرومايسين بنسبة (42.0%). وتبين أن غالبية البكتيريا المعزولة من المرضى مقاومة لمضادات متعددة. توضح النتائج أهمية الوقت في تحديد جمع عينات لتحديد مسببات الأمراض ونمط حساسيتها للمضادات الحيوية قبل البدء في العلاج المضاد للميكروبات في الحالات المصابة